A System Dynamic Simulation Model for Managing the Human Error in Power tools Industries. - Mohd Jamil, Jastini; Mohd Shaharanee, Izwan Nizal (International Journal of Supply Chain Management, 2017)
In the era of modern and competitive life of today, every organization will face the situations in which the work does not proceed as planned when there is problems occur in which it had to be delay. However, human error is often cited as the culprit. The error that made by the employees would cause them have to spend additional time to identify and check for the error which in turn could affect the normal operations of the company as well as the company’s reputation. Employee is a key element of the organization in running all of the activities of organization. Hence, work performance of the employees is a crucial factor in organizational success. The purpose of this study is to identify the factors that cause the increasing errors make by employees in the organization by using system dynamics approach. The broadly defined targets in this study are employees in the Regional Material Field team from purchasing department in power tools industries. Questionnaires were distributed to the respondents to obtain their perceptions on the root cause of errors make by employees in the company. The system dynamics model was developed to simulate the factor of the increasing errors make by employees and its impact. The findings of this study showed that the increasing of error make by employees was generally caused by the factors of workload, work capacity, job stress, motivation and performance of employees. However, this problem could be solve by increased the number of employees in the organization.